2005
DOI: 10.1063/1.1748524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluated Kinetic Data for Combustion Modeling: Supplement II

Abstract: This compilation updates and expands two previous evaluations of kinetic data on elementary, homogeneous, gas phase reactions of neutral species involved in combustion systems [J. Phys. Chem. Ref Data 21, 411 (1992); 23, 847 (1994)]. The work has been carried out under the auspices of the IUPAC Commission on Chemical Kinetics and the UK Engineering and Physical Sciences Research Council. Individual data sheets are presented for most reactions but the kinetic data for reactions of C2, C, ethyl, i-propyl, t-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

158
1,393
16
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,340 publications
(1,579 citation statements)
references
References 0 publications
158
1,393
16
12
Order By: Relevance
“…From experiments, Wantuck et al [42] reported a nonlinear Arrhenius behavior, with the rate constant increasing strongly above 600 K. However, their results have been questioned due to possible interference by thermal dissociation of CH 3 O (R19) at the higher temperatures. For this reason, Baulch et al [34] chose to disregard the data from Wantuck et al in their evaluation of k 19 . It is interesting to note that our theoretical rate constant (denoted by the solid line in Fig.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…From experiments, Wantuck et al [42] reported a nonlinear Arrhenius behavior, with the rate constant increasing strongly above 600 K. However, their results have been questioned due to possible interference by thermal dissociation of CH 3 O (R19) at the higher temperatures. For this reason, Baulch et al [34] chose to disregard the data from Wantuck et al in their evaluation of k 19 . It is interesting to note that our theoretical rate constant (denoted by the solid line in Fig.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…HNC( 1  + ) 188 (Hansel et al 1998) HCN + ( 2 ) 1447 1440 (Baulch et al 2005, Lias et al 1988 This work (MRCI+Q/cc-pVQZ including ZPE) HNC + ( 2  + ) 1336 1349 (Kraemer et al 1992) This work (MRCI+Q/cc-pVQZ including ZPE)…”
mentioning
confidence: 98%
“…Figure 3 compares our calculated reaction rate constants of the three channels with the corresponding values deployed in kinetic models of Dagaut et al [9] and Gudiyella and Brezinsky [11]. These two models incorporate the kinetic parameters that were carried over from the system of n-propane + HO 2 based on the recommended values of Baulch et al [39], from primary and secondary sites and from the system of toluene + HO 2 for benzylic sites [39]. Comparison is also made with our theoretically-derived values for ethylbenzene [22].…”
Section: Abstraction Of Propyl H Atom By Ho 2 Radicalsmentioning
confidence: 99%